2015
DOI: 10.1007/s00894-015-2711-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of an [(Al2O3)4]+ cluster

Abstract: Density functional theory (DFT) has been applied to investigate the structural and electronic properties of an [(Al2O3)4](+) cluster. Since there is no structural data available from experiment, the geometry of the cluster was obtained based on a model which produced the best agreement with vibrational IR-MPD data. A range of different exchange-correlation functionals were tested, and it was concluded that the best spectral agreement was produced using the CAM-B3LYP and B3LYP functionals, respectively. To furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…24 Some ambiguity still exists regarding the exact structure of the gas phase cluster, however, on the basis of NBO analysis, the group of P. M. Kozlowski concluded that, both cation [Al 8 O 12 ] + and neutral [Al 8 O 12 ] systems are most appropriately described as molecules, rather than clusters. 25 Industrial production of ethylene by the dehydration of ethanol is mediated by Lewis acid catalysis of γ-Al 2 O 3 . 3,26 It has been reported that the reaction is inhibited by the formation of surface hydroxyl groups that block the C-H bond cleavage which is essentially involved in the rate limiting step.…”
Section: Introductionmentioning
confidence: 99%
“…24 Some ambiguity still exists regarding the exact structure of the gas phase cluster, however, on the basis of NBO analysis, the group of P. M. Kozlowski concluded that, both cation [Al 8 O 12 ] + and neutral [Al 8 O 12 ] systems are most appropriately described as molecules, rather than clusters. 25 Industrial production of ethylene by the dehydration of ethanol is mediated by Lewis acid catalysis of γ-Al 2 O 3 . 3,26 It has been reported that the reaction is inhibited by the formation of surface hydroxyl groups that block the C-H bond cleavage which is essentially involved in the rate limiting step.…”
Section: Introductionmentioning
confidence: 99%
“…45 Al 8 O 12 can be treated as a molecule. 46 It can accurately reproduce periodic DFT and experimental values of surface relaxation parameters and energies of the α-Al 2 O 3 surface. 47,48 To this end, we constructed five initial configurations for an α-Al 2 O 3 cluster of α-Al 8 O 12 and the repeat unit of cis-1,4-PB (cis-2-butene) shown in Figure 2.…”
Section: ■ Methodologymentioning
confidence: 85%
“…49 CAM-B3LYP is the bestperforming functional for Al 8 O 12 when compared with experimental values of vibrational IR-MPD data. 46 The basis set superposition error (BSSE) was corrected by the Boys− Bernardi method. 50 For the above computations, Gaussian software 51 was employed.…”
Section: ■ Methodologymentioning
confidence: 99%
See 2 more Smart Citations